2020
DOI: 10.1101/2020.04.29.068478
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

anTraX: high throughput video tracking of color-tagged insects

Abstract: Recent years have seen a surge in methods to track and analyze animal behavior. Nevertheless, tracking individuals in closely interacting, group-living organisms remains a challenge. Here we present anTraX, an algorithm and software package for high-throughput video tracking of color-tagged insects. anTraX combines neural network classification of animals with a novel approach for representing tracking data as a graph, enabling individual tracking even in cases where it is difficult to segment animals from one… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 70 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…We therefore systematically studied foraging behavior in the clonal raider ant, Ooceraea biroi, the only non-army ant doryline that can be propagated in the laboratory. In our efforts to establish this species as an experimental model, we have developed high-throughput, automated tracking approaches to monitor individual and collective behavior (Gal et al, 2020;Ulrich et al, 2018). This created the unique opportunity to study doryline foraging behavior quantitatively and under controlled laboratory conditions.…”
Section: Main Textmentioning
confidence: 99%
See 4 more Smart Citations
“…We therefore systematically studied foraging behavior in the clonal raider ant, Ooceraea biroi, the only non-army ant doryline that can be propagated in the laboratory. In our efforts to establish this species as an experimental model, we have developed high-throughput, automated tracking approaches to monitor individual and collective behavior (Gal et al, 2020;Ulrich et al, 2018). This created the unique opportunity to study doryline foraging behavior quantitatively and under controlled laboratory conditions.…”
Section: Main Textmentioning
confidence: 99%
“…Each colony consisted of 25 ants, and each ant was tagged with an ordered pair of color dots that was unique within the colony. Specifically, each ant was painted on her thorax and gaster with one of five colors of oil-paint markers (uni Paint Markers PX-20 and PX-21), a previously-used technique (Gal et al, 2020;Trible et al, 2017;Ulrich et al, 2018). At the end of the experiment, we counted all larvae, and found that each colony had between 20 and 25 larvae.…”
Section: Tagged-ant Experimentsmentioning
confidence: 99%
See 3 more Smart Citations